KESALAHAN SISWA DALAM MENGERJAKAN SOAL MOMENTUM DAN IMPULS - Zulkifli, Andi; Mansyur, Jusman; Syamsu (Universitas Tadulako, 2021)
This study aims to analyze the mistakes made by students in solving problems on momentum and impulse. This research was conducted at SMA Negeri 3 Palu in class XI MIA 3 consisting of 25 students. This research was a qualitative descriptive approach. The data collection instruments used were essay tests and interviews. Respondents were selected based on the ability level of students which were divided into high, medium and low categories. Based on the results of the study showed that the mistakes made by students in solving momentum and impulse questions were still relatively high. This can be seen from the test results which show that there were still so many mistakes made by students. Mistakes that were done by students including translation, conceptual, strategy and counting errors.